A Six-Month Randomized Controlled Trial of Whole Soy and Isoflavones Daidzein on Body Composition in Equol-Producing Postmenopausal Women with Prehypertension. (31st July 2013) - Liu, Zhao-min; Ho, Suzanne C.; Chen, Yu-ming; Woo, Jean
Abstract : Objectives . This paper reported the effects of commonly used whole soy foods (soy flour) and purified daidzein (one of the major isoflavones and the precursor of equol) on changes in anthropometric measurements and body composition in a 6-month double-blind, randomized, placebo-controlled trial among prehypertensive postmenopausal women who are also equol producers. Methods . 270 eligible women were randomized to either one of the three treatments: 40 g soy flour (whole soy group), 40 g low-fat milk powder + 63 mg daidzein (daidzein group), or 40 g low-fat milk powder (placebo group) daily each for 6 months. Anthropometric indicators and body composition were measured before and after intervention. Results . 253 subjects completed the study with good compliance. Urinary isoflavones levels suggested good compliance of subjects with supplementation. Whole soy and purified daidzein had no significant effect on body weight, body mass index (BMI), waist and hip circumferences, waist to hip ratio (WHR), body fat percentage, fat mass, and free fat mass. Conclusion. Six-month consumption of whole soy and purified daidzein at provided dosage had no improvement on body weight and composition compared with isocaloric milk placebo among prehypertensive equol-producing postmenopausal women. This trial is registered with ClinicalTrials.gov NCT01270737 .